Automated animation of quadrupeds using procedural programming technique - Bhatti, Zeeshan; Shah, Asadullah; Waqas, Ahmad; Karbasi, Mostafa (Asian Network for Scientific Information, 2015)
In this research a simple yet efficient means of generating quadruped animation using trigonometric based mathematical equations with expressions were discussed. The technique proposed through this research is based on two tier animation control curve. The base simulation is driven through procedural model using trigonometric sinus and cosine functions to generate a sinusoidal motion curve with control parameters. The trigonometric sinus and cosine functions are used with control attributes to produce involuntary, procedurally generated base animation. In the top layer, animation is manipulated and customized by the animator through custom user controllable manipulators. These manipulators are created through an automated procedural rigging technique, based on forward and inverse kinematics controls. The User is provided with various attributes to control the locomotion gaits and create varying types of gaits from walking, running and trotting with complete custom mechanism to easily extend the base simulation as per requirements through an intuitive Graphical User Interface (GUI).